Administration of 3% Sodium Chloride and Local Infusion Reactions - Michael L. Moritz; Juan C. Ayus; Joel B. Nelson (MDPI AG, 2022)
Three-percent sodium chloride (3% NaCl) is a hyperosmolar agent used to treat hyponatremic encephalopathy or other cases of increased intracranial pressure. A barrier to the use of 3% NaCl is the perceived risk of local infusion reactions when administered through a peripheral vein. We sought to evaluate reports of local infusion reactions associated with 3% NaCl over a 10-year period throughout a large healthcare system. A query was conducted through the Risk Master database to determine if there were any local infusion reactions associated with peripheral 3% NaCl administration throughout the entire UPMC health system, which consists of 40 hospitals with 8400 licensed beds, over a 10-year time period from 14 May 2010 to 14 May 2020. Search terms included infiltrations, extravasations, phlebitis, IV site issues, and IV solutions. There were 23,714 non-chemotherapeutic and non-contrast-associated intravenous events, of which 4678 (19.7%) were at UPMC Children's Hospital. A total of 2306 patients received 3% NaCl, of whom 836 (35.8%) were at UPMC Children's Hospital. There were no reported local infusion reactions with 3% NaCl. There were no reported local infusion reaction events associated with 3% NaCl in a large healthcare system over a 10-year period. This suggests that 3% NaCl can be safely administered through a peripheral IV or central venous catheter.